2022
DOI: 10.3390/ijerph19052762
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Target Hazard Quotients and Potential Health Risks for Toxic Metals and Other Trace Elements by Consumption of Female Fish Gonads and Testicles

Abstract: The aim of this study was to assess the risk to consumers associated with the intake of toxic metals and other trace elements in diets that include the female gonads, testicles, and muscles of four popular freshwater fish species in Poland—common bream (Abramis brama L.), European perch (Perca fluviatilis L.), common roach (Rutilus rutilus L.), and northern pike (Esox Lucius L.). The following methods were used to determine the elements: GF-AAS (Pb, Cd); CV-AAS (Hg); ICP-AES (Zn, Fe, Mn, Cu, Ni, Li, Cr, Al). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The excess value was expressed by hazard quotients [HQ] [33][34][35], where HQ = actual gross content [mg/kg]/MPC [mg/kg]. The HQ levels were extremely high and achieve 12 830 times in the case of chromium.…”
Section: Environmental Assessmentmentioning
confidence: 99%
“…The excess value was expressed by hazard quotients [HQ] [33][34][35], where HQ = actual gross content [mg/kg]/MPC [mg/kg]. The HQ levels were extremely high and achieve 12 830 times in the case of chromium.…”
Section: Environmental Assessmentmentioning
confidence: 99%
“…Health risk assessment tests were used to estimate the probability in which people can be affected after exposure for a certain period of time. Target hazard quotient (THQ), total target hazard quotient (TTHQ) and cancer risk (CR) were determined as proposed by United States Environmental Protection Agency (USEPA 2003) [38] , [42] and Ain et al [2] . Provisional maximum tolerable daily (PMTDI) intake per average body weight of adults were calculated to estimate the number of metals ingested daily [29] , [38] .…”
Section: Methodsmentioning
confidence: 99%
“…To determine the threat to human health stemming from the intake of carcinogenic and non-carcinogenic elements. The U.S. Environmental Protection Agency (USEPA) introduced the target hazard quotient (THQ) and hazard index (HI) Pokorska-Niewiada et al [42] and Ain et al [2] . It is the ratio between the estimated daily intakes to the reference dose which when consumed do not accelerate any potential health effect estimated by length, weight, frequency of exposure, body weight (70 kg for an adult) and the amount consumed per day in grams Nkansah et al [38] , and Kortei et al [29] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis in comparison with MPC (Table 4) showed that all waste samples exceed the declared Kazakhstan levels of MPC based on the heavy metal contents. The excess value was expressed by hazard quotients (HQ) (Ikhajiagbe & Ogwu, 2020;Pokorska-Niewiada et al, 2022;Pongpiachan et al, 2018), where HQ = actual gross content (mg/kg) / MPC (mg/kg). The HQ levels were very high and achieve 10.71 in the case of nickel.…”
Section: Introductionmentioning
confidence: 99%